Postembryonic Fish Brain Proliferation Zones Exhibit Neuroepithelial-Type Gene Expression Profile. (14th March 2017) - Dambroise, Emilie; Simion, Matthieu; Bourquard, Thomas; Bouffard, Stéphanie; Rizzi, Barbara; Jaszczyszyn, Yan; Bourge, Mickaël; Affaticati, Pierre; Heuzé, Aurélie; Jouralet, Julia; Edouard, Joanne; Brown, Spencer; et al.
Abstract : In mammals, neuroepithelial cells play an essential role in embryonic neurogenesis, whereas glial stem cells are the principal source of neurons at postembryonic stages. By contrast, neuroepithelial-like stem/progenitor (NE) cells have been shown to be present throughout life in teleosts. We used three-dimensional (3D) reconstructions of cleared transgenic wdr12 :GFP medaka brains to demonstrate that this cell type is widespread in juvenile and to identify new regions containing NE cells. We established the gene expression profile of optic tectum (OT) NE cells by cell sorting followed by RNA-seq. Our results demonstrate that most OT NE cells are indeed active stem cells and that some of them exhibit long G2 phases. We identified several novel pathways (e.g., DNA repair pathways) potentially involved in NE cell homeostasis. In situ hybridization studies showed that all NE populations in the postembryonic medaka brain have a similar molecular signature. Our findings highlight the importance of NE progenitors in medaka and improve our understanding of NE-cell biology. These cells are potentially useful not only for neural stem cell studies but also for improving the characterization of neurodevelopmental diseases, such as microcephaly.